Can Electronic Vote Bring Workers Closer to Trade Unions? The Case of Portuguese Teachers - Raquel Rego; Ramos, Vasco (Employee Responsibilities and Rights Journal, 2020)
Can digital devices enhance participation? Can the electronic ballot help trade unions in involving different categories of members in their decision-making processes and extend their representativeness? Trade union crisis is largely a legitimacy problem, as unions are representing mostly older and permanent workers. Simultaneously, the enthusiasm towards the internet as a mean to union revitalization seems to have waned somewhat. It was against this backdrop that we decided to conduct a survey of schoolteachers in Portugal and focus on the potential impact of a digital device to engage workers in union life. The survey sought to examines how the electronic ballot could be used as a tool to help decision-making, being aware of the different interests in play, and contributing to the increase of participation within trade unions. Our findings show negligible differences between teachers according to contractual status although non-unionized and precarious workers prove to be less receptive to the use of the electronic ballot.